DEVELOPING METHODOLOGICAL ASPECTS OF INTEGRATED REPORTING: IMPLEMENTATION OF THE EUROPEAN EXPERIENCE (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article proves that the implementation of integrated reporting in Ukraine is an essential proof of the country's integration into the global and European societies. The purpose of the article is to develop methodological recommendations for improving the process of forming integrated reporting in Ukraine based on the implementation of European experience. As a result of the analysis of integrated reporting practices in the world and in Ukraine, it is determined that the formation of IR is a widespread global practice. It is emphasised that in Ukraine, the implementation of IR is not a widespread practice due to certain difficulties associated with incomplete understanding of its benefits by the management of enterprises. During the analysis of integrated reporting formation organization, a characterization of integrated reporting according to Sustainability Accounting Standards Board (SASB) standards, CSRD reports, and ESG reports is provided. The main problems and challenges that arise in the formation of reporting under these standards are identified. The main ways to improve the formation of IR are identified, including creation of a management system for the formation and audit of integrated reporting; improvement of the regulatory environment for reporting and dissemination of integrated thinking; legislative establishment of a phased introduction of the mandatory preparation of integrated reporting for enterprises; development of a National Integrated Reporting Formation Standard to align the content and structure of IR in line with the requirements of international standards; creation of a system of professionalism. Algorithms for performing the sub-stage "Organisation of Integrated Reporting" were clarified; the content of the "Risks" section was developed. Directions for improving the interaction between structural units of enterprises in the process of forming IR are developed. It is proposed to introduce and use modern information technologies in the preparation, analysis and monitoring of integrated reporting. The article reveals approaches to optimisation of interaction with stakeholders, which include development of a concept for organisation of interaction with stakeholders; formation of a list of stakeholders and disclosure of their interests, their constant accounting and updating of data; planning of main activities for interaction with stakeholders
Keywords: integrated reporting; European experience; capital; business; model; stakeholders; methodological aspects; standards